The role of AI and ICT in Education and translation: How will it reshape us? - Arta Këpuska; Kokaj, Agon; Ymeri, Mejreme (Edelweiss Applied Science and Technology, 2025)
Artificial Intelligence (AI) and machine learning are two interconnected concepts that have continued to reshape education, teaching, and research. This study explores how AI is being used to support students, improve teaching, and assist researchers and translators in their daily work. A survey was conducted with 200 participants, including educators, translators, engineers, and AI researchers, to better understand the impact of AI tools. Regarding research, many international and professional language interpreters have started to argue that AI is helping to make their lives easier. Similarly, the results show that AI is helping students with difficult tasks and is being used in many educational settings to make learning more personalized and accessible. In the field of translation, professionals report that AI is making their work easier, especially when human translators are not available or are too expensive. AI machine learning models can be used to address this situation, particularly in international conferences. The study concludes that AI is and will continue to be cost-oriented for many professionals in different fields; however, human input remains important to ensure quality, accuracy, and cultural understanding, especially in education and language translation.